How Does Spousal Education Matter? Some Evidence from Cambodia - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2002)
An econometric analysis of the World Food Programme Civil Insecurity Baseline Survey (1998) and Cambodia Socio-Economic Survey (1999) data is undertaken to examine the role of education and literacy in explaining household expenditure, as hypothesized in human capital theory where education is an investment with returns in the form of income. Explanatory variables were selected from a large set of observed variables by a systematic procedure to avoid the bias arising from arbitrary model selection. Spousal education and literacy are found to be significant explanatory variables in the determination of household expenditure, exceeding even the coefficients attached to the head of household. This suggests that educated and literate spouses may have a significant unobserved role in household consumption decisions and income determination in Cambodia. This finding builds on existing international literature on the importance of maternal and girls’ education in economic development and offers a number of important policy implications.